Study of the Public Health Impact Due to Environmental Pollution by Mining Activities in the District. Berau – East Kalimantan, in the perspective of Law No. 23 of 2009 concerning Environmental Protection and Management - Handono, Totok; Santoso, Aris Prio Agus; Rezi, Rezi (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
Mining activities in Berau Regency, East Kalimantan, have made a significant contribution to the economy, but have also had a negative impact on the environment and public health. This research aims to examine the impact on public health due to environmental pollution by mining activities, as well as the effectiveness of implementing Law No. 23 of 2009 concerning Environmental Protection and Management. The research uses a normative and empirical juridical approach using interview, observation and document analysis methods. The research results show that there is a relationship between environmental pollution and increased morbidity and mortality in communities around the mine. The conclusion of this study recommends improving environmental management and implementing public health protection policies.